2022
DOI: 10.1111/jph.13152
|View full text |Cite
|
Sign up to set email alerts
|

Identification and genetic diversity ofFusarium sacchariassociated with pokkah boeng disease of sugarcane in Northeast Brazil

Abstract: Isolates from the Fusarium fujikuroi species complex, mainly F. sacchari, have been reported to be the causal agents of pokkah boeng in sugarcane in Brazil. However, inadequate information was available on the occurrence and genetic diversity of F. sacchari in Northeast Brazil, which is a limiting factor on management. Thus, isolates of F. subglutinans sensu lato from sugarcane plants with symptoms of pokkah boeng were evaluated using the sexual cross-fertility to determine species. All the isolates produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The pathogenicity and toxicity of Fusarium is well known [59]. Previous studies reported that Fusarium causes PBD in sugarcane [5][6][7][8][9][10][11]. In addition, Ramichloridium, Scleroramularia, Phaeosphaeriopsis, Sarocladium, Zygophiala, and Gibberella are reported as pathogens in bananas [60], apple and pawpaw [61], Butcher's Broom (Ruscus aculeatus) [62], rice [63], apple [64], and maize [65].…”
Section: Endophytic Microbial Community Composition In the Stems Of T...mentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenicity and toxicity of Fusarium is well known [59]. Previous studies reported that Fusarium causes PBD in sugarcane [5][6][7][8][9][10][11]. In addition, Ramichloridium, Scleroramularia, Phaeosphaeriopsis, Sarocladium, Zygophiala, and Gibberella are reported as pathogens in bananas [60], apple and pawpaw [61], Butcher's Broom (Ruscus aculeatus) [62], rice [63], apple [64], and maize [65].…”
Section: Endophytic Microbial Community Composition In the Stems Of T...mentioning
confidence: 99%
“…PBD is a serious fungal disease in sugarcane worldwide. It is caused by various Fusarium spp., mainly F. verticillioides [5], F. sacchari [6], F. proliferatum [7], F. subglutinans [8], F. oxysporum [9], F. fujikuroi [10], and F. andiyazi [11]. Their intermediate hosts can be rice, sorghum, corn, banana, and pumpkin [12][13][14].…”
Section: Introductionmentioning
confidence: 99%